Don't let him in eaudiobook A novel. - Jewell, Lisa (Simon & Schuster Audio, 2025)
From #1 New York Times bestseller Lisa Jewell, an author "at the very top of her game" (Lucy Foley)—three women are connected by one man in this kaleidoscopic thriller. "Who are you? Who are you really?" Nick Radcliffe is a man of substance and good taste. He has a smile that could melt the coldest heart and a knack for putting others at ease. He's just what Nina Swann needed in her life after her husband's unexpected death. But to Nina's adult daughter, Ash, Nick seems too slick, too polished, too good to be true. Without telling her mother, Ash begins digging into Nick's past. What she finds is more than unsettling... "Because there are things that don't make sense, and I've been so patient, so very patient..." Martha is a florist living in a neighboring town with her infant daughter and her devoted husband Alistair. But lately, Alistair has been traveling more and more frequently for work, disappearing for days at a time. When Martha questions him about his frequent absences, he always has a legitimate explanation, but Martha can't share the feeling that something isn't right. "You know that's mad, don't you? I'm your husband. We know everything there is to know about each other." Nina, Martha, and Ash are on a collision course with a shocking truth that is far darker than anyone could have imagined. And all three are about to wish they had heeded the same warning: Don't let him in. But the past won't stay buried forever.